Hard Skill Sebagai Faktor Dominan Kesiapan Kerja Di Era Industri 4.0 - Riyanto, Fery; Astuti, Sih Dari; Mahmud, Mahmud; Panjaitan, Roymon (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim : This study aims to test soft skills and hard skills and competencies to determine job readiness in the industrial era 4.0 in generation z students at public and private universities in the city of Semarang. Design/Methode/Approach : The sample technique used was proportional random sampling. Data collected using a survey method using a questionnaire. This study uses Structural Equation Modeling (SEM) data analysis techniques which are operated using the AMOS 24 program. Research Finding : Hard Skills have a direct effect on Work Readiness in the industrial era 4.0. 2) Soft Skills have a direct effect on Work Readiness in the industrial era 4.0. 3) Hard Skills have no effect on Work Readiness in the industrial era 4.0 through Competence as a mediating variable. 4) Soft Skills have an indirect effect on work readiness in the industrial era 4.0 through competence as a mediating variable. Theoretical contribution/Originality : Generation Z students can be well received in the world of work, and are able to succeed in the world of work, apart from the hard skills they have, of course from the soft skills they have. Practitionel/Policy implication : The practical implications of this research have the potential to prove that high curiosity in seeking knowledge, experience and enthusiasm is important to compete in preparing to work in the industrial era 4.0. Research limitation : This research was only conducted by students in the city of Semarang and research is still limited to a short time or data using cross-sectional data.